Comparative analysis of rare and heavy metals recovery from waste by isolated, collection and types of microbial strains - Васильєва, Т. В. (Problems of Environmental Biotechnology, 2015)
A group chemolithotrophic acidophilus microorganisms – representatives of the genera Acidithiobacillus and Sulfobacillus are the most active group of microorganisms in aboriginal consortium substrates coal tailing and fly ash from burning coal. A comparison of the oxidative activity of new isolated strains MFLv6 and MFLad5 with highly active collection (A. ferrooxidans UCМ468) and typal (A. ferrooxidans ATCC 23270) strains in terms of the extraction of rare and heavy metals from man-made waste are made, MFLv6 and MFLad5 resistance to heavy metals, which are part of these wastes, are made. Higher oxidative activity and resistance to heavy metal ions of new strains compared with typal and collection strains A. ferrooxidans installed. Minimum inhibitory concentrations of heavy and toxic metals installed and a series of metal on the negative impact on the growth of isolated strains are made. It is shown that the minimum concentration of metals in which growth occurs even strains, several times higher than their fixed content of man-made waste. Studies indicate the need for targeted selection of strains that are resistant to the toxic compounds and can oxidize various mineral substrates, as well as their adaptation to the new substrate for the extraction of rare and heavy metals.